Phytochemical Investigation and In Vitro Antimicrobial Activity of Centella asiatica (L.) Urban. A potent Antijaundice medicinal plant - Chandra Sekhar Panathula,; MD Mahadev,; CV Naidu, (International Journal of Phytomedicine, 2014)
Centella asiatica (L.) is also known as Indian penny wort is a small creeping herbaceous plant belongs to the plant Apiaceae. This plant has been referred in the ancient traditional Indian ayurvedic medicine system about 3000 year’s age. This herb is antidiabetic, antitumor and antidiuretic used in the treatment of jaundice, asthma, bronchitis, dropsy, kidney troubles and leprosy diseases. An investigation was carried out to study the antibacterial activity of Centella asiatica of five different solvent extracts from leaf, stem and roots against selected laboratory bacterial pathogens such as Bacillus subtilis, Staphylococcus aurius, Pseudomonas aurigenosa, Escherichia coli, Klebsiella pnemoniae and Salmonella typhi by agar diffusion method. Zone of inhibition was measured (mm) were compared with standard antibiotics such as kanamycin, cefotoxime, penicillin. The organic solvents such as ethanol, methanol, petroleum ether, chloroform and aqueous extracts were employed. Among all the extracts, methanolic extracts of leaf has showed maximum antibacterial activity against Bacillus subtilis, Salmonella typhi. Phytochemical screening methods were also done to identify the major secondary metabolites in the species such as glycosides, terpenoids, alkaloids, phenolics and tannins. In addition to that the comparative analysis of phenols and tannins of both in conventional plants and in in vitro propagated plants were also traced.